1991
DOI: 10.1203/00006450-199110000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Stimulated GM-CSF Production and GM-CSF Gene Expression but Normal Numbers of GM-CSF Receptors in Human Term Newborns Compared with Adults

Abstract: ABSTRACT. We investigated cord and adult production of granulocyte-macrophage colony-stimulating factor (GM-CSF), expression of GM-CSF mRNA from unstimulated and activated mononuclear cells, and the affinity and presence of GM-CSF receptors on mature effector cells in an attempt to better understand the underlying pathophysiology of altered neonatal host defense. Utilizing '251-GM-CSF as a ligand, Scatchard analysis revealed the presence of a single class affinity GM-CSF receptor with similar binding character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 7 publications
5
40
1
1
Order By: Relevance
“…Additionally, our study did not determine whether the decrease in G-CSF or IL-3 production from cord MNC was secondary to a decrease per MNC or a decrease in the specific subpopulation of G-CSF and IL-3 producing MNC. These results are consistent with our previous findings demonstrating negligible amounts of cord serum GM-CSF and decreased GM-CSF production after stimulation of cord MNC (32).…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, our study did not determine whether the decrease in G-CSF or IL-3 production from cord MNC was secondary to a decrease per MNC or a decrease in the specific subpopulation of G-CSF and IL-3 producing MNC. These results are consistent with our previous findings demonstrating negligible amounts of cord serum GM-CSF and decreased GM-CSF production after stimulation of cord MNC (32).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are in keeping with those of Cairo et al (37,38), who were unable to demonstrate G-CSF or GM-CSF in cord sera of full-term neonates using an ELISA, but our results are at variance with those of Laver et al (36), who found high levels of both G-CSF and GM-CSF in full-term cord sera using a bioassay. This discrepancy may be accounted for by the different assay techniques used.…”
Section: Discussioncontrasting
confidence: 57%
“…20,21,30,39,40 The basal concentrations of GM-CSF in neonatal sera are negligible, and decreased GM-CSF expression and production may contribute to the development of neutropenia. 13,14 In a recent clinical trial, administration of recombinant human GM-CSF to premature infants was well-tolerated, and peripheral blood PMN counts and CR3 receptor expression were significantly increased. 30 Although GM-CSF may increase N-PMN count and function, type III GBS is most efficiently killed by PMNs when opsonized with complement and capsular polysaccharide-specific Ab.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the previously demonstrated priming for oxidative metabolism that occurs with GM-CSF treatment may have contributed to the enhanced microbial killing observed. 19 Although the production of GM-CSF by neonatal mononuclear cells may be reduced, [12][13][14] it also has been shown that the bactericidal activity of N-PMNs can be increased by GM-CSF. 19 Deficiencies in neonatal host defenses contribute to susceptibility to GBS infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation